Peripheral and Central Venous Blood Glucose Concentrations in Dogs and Cats with Acute Arterial Thromboembolism. (16th July 2014) - Klainbart, S.; Kelmer, E.; Vidmayer, B.; Bdolah‐Abram, T.; Segev, G.; Aroch, I.
<x xml:space="preserve">Abstract</x> Background Acute limb paralysis because of arterial thromboembolism (ATE) occurs in cats and less commonly in dogs. ATE is diagnosed based on physical examination findings and, occasionally, advanced imaging. Hypothesis/Objectives Peripheral, affected limb venous glucose concentration is decreased in ATE, whereas its systemic concentration is within or above reference interval. Animals Client‐owned cats and dogs were divided into 3 respective groups: acute limb paralysis because of ATE (22 cats and 9 dogs); acute limb paralysis secondary to orthopedic or neurologic conditions (nonambulatory controls; 10 cats and 11 dogs); ambulatory animals presented because of various diseases (ambulatory controls; 10 cats and 9 dogs). Methods Prospective observational, clinical study. Systemic and local (affected limb) blood glucose concentrations were measured. Their absolute and relative differences (ΔGlu and %ΔGlu, respectively) were compared among groups. Results ΔGlu and %ΔGlu were significantly higher in the ATE cats and dogs groups, compared to both of their respective controls (P < .0001 and P < .001, respectively). No significant differences were observed between the control groups. Receiver operator characteristics analysis of ΔGlu and %ΔGlu as predictors of ATE had area under the curve of 0.96 and 0.99 in cats, respectively, and 1.00 and 1.00, in dogs, respectively. ΔGlu cutoffs of 30 mg/dL and 16 mg/dL, in cats and dogs, respectively, corresponded to sensitivity and specificity of 100% and 90% in cats, respectively, and 100% in dogs. Conclusions and Clinical Importance ΔGlu and %ΔGlu are accurate, readily available, diagnostic markers of acute ATE in paralyzed cats and dogs.